KEESAAN GEREJA MENURUT CALVIN DALAM INSTITUTIO 1536 - Agustinus M. L. Batlajery (Studia Philosophica et Theologica, 2011)
This writing focuses on the ecclesiology of Calvin, especially his concept on the unity of the church in The Institutes of the Christian Religions (1536), the first version of the Institutes. In this Institutes we see that the primary accent of his ecclesiology falls on unity. By stressing on the catholicity and universality of the church, Calvin showed his clear thoughts about the unity of the church and the way to achieve it. For him, the way towards the unity of the church was not, first of all, an issue of building up a new structure or a bureaucratic organization for the church. It had to start with the basic issue of faith in Jesus Christ as the Head of the church, which is Christ’s body. Calvin’s view on unity is based on his vision of true catholicity. Catholicity means unity. In order words, Calvin envisioned the unity of the church in a spiritual way